2022
DOI: 10.3390/md20120785
|View full text |Cite
|
Sign up to set email alerts
|

Fillet Fish Fortified with Algal Extracts of Codium tomentosum and Actinotrichia fragilis, as a Potential Antibacterial and Antioxidant Food Supplement

Abstract: With respect to the potential natural resources in the marine environment, marine macroalgae or seaweeds are recognized to have health impacts. Two marine algae that are found in the Red Sea, Codium tomentosum (Green algae) and Actinotrichia fragilis (Red algae), were collected. Antibacterial and antioxidant activities of aqueous extracts of these algae were evaluated in vitro. Polyphenols from the extracts were determined using HPLC. Fillet fish was fortified with these algal extracts in an attempt to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In fact, it has been reported that antioxidants could cause neutrophils to phagocytose C3‐opsonized pathogens more effectively by reducing the damage to their own membranes caused by free radicals created in the respiratory burst (Boxer, 1986). The silk microparticles used in our experiment have an antioxidant capacity similar or superior to that observed in other supplements capable of positively modulating immune capacity, such as plant extracts (García‐Beltrán et al, 2018, 2020b), algae extracts (Hafez et al, 2022) or yeast strains (Reyes‐Becerril et al, 2021) used in fish. In the articles, supplementation with antioxidants positively modulated the immune response in fish, increasing the parameters analysed, such as phagocytosis and respiratory burst (García‐Beltrán et al, 2018, 2020b; Hafez et al, 2022; Reyes‐Becerril et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…In fact, it has been reported that antioxidants could cause neutrophils to phagocytose C3‐opsonized pathogens more effectively by reducing the damage to their own membranes caused by free radicals created in the respiratory burst (Boxer, 1986). The silk microparticles used in our experiment have an antioxidant capacity similar or superior to that observed in other supplements capable of positively modulating immune capacity, such as plant extracts (García‐Beltrán et al, 2018, 2020b), algae extracts (Hafez et al, 2022) or yeast strains (Reyes‐Becerril et al, 2021) used in fish. In the articles, supplementation with antioxidants positively modulated the immune response in fish, increasing the parameters analysed, such as phagocytosis and respiratory burst (García‐Beltrán et al, 2018, 2020b; Hafez et al, 2022; Reyes‐Becerril et al, 2021).…”
Section: Discussionsupporting
confidence: 66%
“…Seaweeds are also rich sources of iodine, a vital mineral for thyroid function. The iodine extracted from seaweeds can be used in iodized salt and dietary supplements to address iodine deficiency [ 166 ].…”
Section: Sustainable Seaweed Cultivation and Compounds Extractionmentioning
confidence: 99%
“…The FRAP and CUPRAC results are influenced by the presence of flavonoid compounds in the samples that can help the metal ions reduction process such as iron and copper (Benavente et al, 1997). Actinotrichia fragilis has total flavonoid content of 3.86±1.02 mg/g of extract (Abd El Hafez et al, 2022). The CUPRAC assay is highly efficient for glutathione and thiol types of antioxidants which cannot be detected in FRAP method (Apak et al, 2005).…”
Section: Total Phenolic Content and Antioxidant Activity Of A Fragili...mentioning
confidence: 99%